PENGUATAN MINAT WIRAUSAHA PADA PONDOK PESANTREN BAHRUL UULUM - Wahyudin, Wahyudin; Setyorini, Chirstina Tri; Pratiwi, Umi; Indira Kusuma, Poppy Dian; Lestari, Puji (Jurnal Pengabdian Bisnis dan Akuntansi, 2023)
Islamic boarding schools are a type of Islamic education in Indonesia that is traditional and has the special characteristic of being a place for parents to send their children to school. The entrepreneurial spirit and spirit in Islamic boarding schools needs to be cultivated as an effort to increase economic resilience. This community service aims to foster an entrepreneurial spirit in the Islamic boarding school, namely the Bhrul Uulum Islamic Boarding School. The activity participants consisted of teachers and managers of the Bahrul Uulum Purbalingga Islamic Boarding School Foundation, Central Java. The training method is implemented by providing training, mentoring on entrepreneurial techniques and question and answer discussions. The results of the activity are expected to be able to provide new knowledge and knowledge for the participants and increase their self-confidence to try entrepreneurshi